Substrate-triggered SCR device for on-chip ESD protection in fully silicided sub-0.25-μm CMOS process. - Ming-Dou Ker
The turn-on mechanism of a silicon-controlled rectifier (SCR) device is essentially a current triggering event. While a current is applied to the base or substrate of the SCR device, it can be quickly triggered into its latching state. In this paper, a novel design concept to turn on the SCR device by applying the substrate-triggered technique is first proposed for effective on-chip electrostatic discharge (ESD) protection. This novel substrate-triggered SCR device has the advantages of controllable switching voltage and adjustable holding voltage and is compatible with general CMOS processes without extra process modification such as the silicide-blocking mask and ESD implantation. Moreover, the substrate-triggered SCR devices can be stacked in ESD protection circuits to avoid the transient-induced latch-up issue. The turn-on time of the proposed substrate-triggered SCR devices can be reduced from 27.4 to 7.8 ns by the substrate-triggering technique. The substrate-triggered SCR device with a small active area of only 20 μm × 20 μm can sustain the HBM ESD stress of 6.5 kV in a fully silicided 0.25-μm CMOS process.
Keywords: 0.25 micron; 20 micron; 6.5 kV; 7.8 ns; Adjustable holding voltage; Controllable switching voltage; Current triggering event; Electrostatic discharge protection; Fully silicided CMOS process; Latching state; On-chip ESD protection; Silicon-controlled rectifier device; Substrate-triggered SCR device; Turn-on mechanism